Non-Discrimination Principle in Trade-Related Aspects of Intellectual Property Rights - Its Function, Scope and Effects on Negotiating Preferential Trade Agreements - Trojanová, Kamila; Štěrbová, Ludmila, 1957-; Müller, Štěpán, 1945-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The thesis focuses on the non-discrimination principle in international IPR treaties, explaining the background in terms of historical developments prior to the TRIPS Agreement, the negotiations of the TRIPS Agreement and the theory of the non-discrimination principle, covering both national treatment and the most-favoured nation principle. It analyses the non-discrimination principle in other important international treaties: the Paris Convention, the Berne Convention and the Rome Convention. The third chapter is devoted to the sources of the TRIPS-plus provisions. A special attention is paid to the intellectual property in international investment agreements. The research presents the regulation of the intellectual property from the perspective of the EU as well as in the US trade policy. The findings build upon the analyses of the IP provisions of the EU, US and selected other trade agreements. Thereupon, the thesis presents a comprehensive typology of IP provisions in preferential trade agreements. Each type of the provisions is explained in detail and is illustrated by the exact wording of selected preferential trade agreements. The author concludes with the analysis of the scope and possible impact of the non-discrimination principle in the trade-related aspects of intellectual property rights.
Vedoucí práce: Ludmila Štěrbová
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor disert. práce]; disertace; dissertations